2017
DOI: 10.2334/josnusd.16-0820
|View full text |Cite
|
Sign up to set email alerts
|

Continuous combined intake of polydextrose and lactitol stimulates cecal fermentation and salivary IgA secretion in rats

Abstract: Immunoglobulin A (IgA), which plays an important role in infection defense, is upregulated in the large intestine and oral cavity through dietary fiber intake. However, the mechanism underlying salivary IgA increase through dietary fiber intake remains unknown. This study investigated timedependent effects of non-absorbable polydextrose (PDX) and lactitol intake on salivary IgA secretion and cecal fermentation. Five-week-old rats were fed a fiber-free diet with or without 25 g/kg PDX and 25 g/ kg lactitol for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Furthermore, it has been reported that the ingestion of PDX increases the IgA concentration in cecal digesta but simultaneously decreases the SCFA concentrations [20]. These results were replicated in our previous study, in which rats were fed a diet containing a combination of PDX and lactitol [21].…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…Furthermore, it has been reported that the ingestion of PDX increases the IgA concentration in cecal digesta but simultaneously decreases the SCFA concentrations [20]. These results were replicated in our previous study, in which rats were fed a diet containing a combination of PDX and lactitol [21].…”
Section: Introductionsupporting
confidence: 80%
“…Salivary IgA flow rate (μg/10 min) was calculated by multiplying salivary IgA concentration (μg/mL) by salivary flow rate (mL/10 min) [ 23 ]. The salivary IgA flow rate normalized on the submandibular gland tissue weight (µg/10 min/g) was calculated as described in our previous studies [ 21 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mannitol can work as an antioxidant and protect hyaluronic acid in the skin [96]. Lactitol has been reported to stimulate secretory IgA production [97]. Erythritol causes no increase in blood serum glucose level [82].…”
Section: Discussionmentioning
confidence: 99%